Factors influencing implementation of the Ministry of Health-led private medicine retailer programmes on malaria in Kenya - Rowa, Y; Abuya, T; Mutemi, W; Ochola, S; Molyneux, S; Marsh, V (BioMed Central, 2010)
Background: Kenya has experienced a number of retail sector initiatives aimed at improving access to antimalarial medicines. This study explored stakeholders' perceptions of the role of private medicine retailers (PMRs), the value and feasibility of programme goals, perceived programme impact, factors influencing implementation and recommendations in three districts of Kenya. Methods: This study was part of a larger evaluation of PMR programmes, including quantitative and qualitative components. The qualitative research was conducted to assess implementation processes and actors' experiences in the programmes, through focus group discussions with trained PMRs and mothers of children under five years, and in-depth interviews with programme managers, trainers and co-trainers. Results: PMRs were perceived to provide rapid cheap treatment for non-serious conditions and used as a deliberate and continuously evaluated choice between different treatment sources. All stakeholders supported programme goals and most PMRs described increased customer satisfaction, more rational purchasing of medicine stock and increased medicine sales after participation. Factors undermining programme implementation included a lack of MoH resources to train and monitor large numbers of PMRs, the relative instability of outlets, medicines stocked and retail personnel, the large number of proprietary brands and financial challenges to retailers in stocking antimalarial medicines, and their customers in buying them. Unambiguous national support and a broad range of strategies are important to strengthen the feasibility of change in OTC antimalarial use. Conclusions: Understanding the context and implementation processes of PMR programmes and the perspectives of key actors are critical to identifying measures to support their effective implementation. Financial barriers underlie many described challenges, with important implications for policies on subsidies in this sector. In spite of barriers to implementation, increased exposure to programme activities promoted trust and improved relationships between PMRs and their clients and trainers, strengthening feasibility of such interventions. Public information can strengthen PMR training programmes by engaging local communities and may facilitate performance monitoring of PMRs by their clients.